Development of a step-based process planning application protocol for PCB assembly - Lim, Jit Hai. (2009)
The shift in manufacturing paradigm to Computer Integrated Manufacturing (CIM) to improve overall manufacturing productivity has been hampered by the incompatibility of the available computer systems. This incompatibility is well known and international concerted effort to standardize a robust and reliable specification saw the development of STEP (STandard for Exchange of Product model data) by ISO which besides enabling a smooth exchange and sharing of product life cycle data between different computer systems and environment have opened up opportunity for systems integration. Such capability have made STEP an important technology for CIM. Thus, it is important to learn STEP and its methodology for the purpose of CIM application regardless of its extend to improve overall manufacturing productivity. This dissertation serves to learn the STEP methodology by using it to develop a STEP-based PCB process planning Application Protocol (AP) for PCB assembly. A step by step development of the AP which entails the use of IDEFO, IDEF1X, and EXPRESS Language (ISO 10303-11) is presented. The mapping of the EXPRESS model is then implemented using the ISO 10303-21 constructs where all the entities in the model are mapped into the neutral STEP physical file format. The implication of STEP on the manufacturing sector is also discussed in view of it as the "missing key" to CIM.